Mitigating thermal runaway propagation of pouch-type lithium-ion batteries - Muhammad Ahshiq Bin V M Abdul Muthaliff (Nanyang Technological University, 2023)
Lithium-Ion Batteries (LIB) are a common power source for various applications. Amongst the different types of LIB, pouch cells are widely adopted due to their compact design and excellent performance. However, when subjected to extreme conditions, pouch cells ignite and explode in a phenomenon known as thermal runaway (TR). If multiple pouch cells are present, TR can propagate from the trigger to the neighbouring cell, resulting in catastrophic effects.